Implementación del sistema de gestión de seguridad y salud en el trabajo con base en el decreto 1072 del 2015 y resolución 0312 del 2019 en la empresa carnes y embutidos Santa Rita S.A.S. (2020)
The present degree work related below, shows and defines each of the steps used to achieve the implementation of the Occupational Safety and Health System based on Decree 1072 of 2015 and Resolution 0312 of 2019 in the company Carnes y Sausages Santa Rita SAS The process of continuous improvement of a company must be aligned with the management systems, which have as a principle the PHVA cycle (Plan, Do, Verify, Act), follow instructions and processes for their respectful compliance. The Occupational Health and Safety Management System consists of the prevention of any injury, illness or accident due to labor conditions, causing protection and health care for workers; it is based on a logical and phased process to define, evaluate and prevent any risk.